The Influence of Motivation and Work Discipline on Teacher Performance in SMP Negeri 1 Sembawa - Anggreani, Trisna; Fitria, Happy; Missriani (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine the significance of the effect of Motivation and Work Discipline on Teacher Performance in Junior High School Number 1 of Sembawa. This type of research is quantitative descriptive. Samples in the study were 63 respondents wits data collection techniques in the form of a questionnaire (questionnaire). The results showed that: 1) there was a siginificant influence of motivation on teacher performance, 2) there was a significant effect of work discipline on teacher performance, 3) there was a significant effect between motivation and work discipline on teacher performance.